30.8k views
3 votes
2b (squared) + 3b (squared) - 3b

2 Answers

6 votes

Answer:

-b

Explanation:

User Melix
by
5.1k points
3 votes

Answer:

A

Explanation:

Given

\sqrt[]{50a^6b^7}

50a

6

b

7

Therefore, solving:

\sqrt[]{50}\sqrt[]{a^6}\sqrt[]{b^7}

50

a

6

b

7

Simplify

\begin{gathered}\begin{gathered} \sqrt[]{50}=5\sqrt[]{2} \\ \sqrt[]{a^6}=a^3 \\ \sqrt[]{b^7}=b^3\sqrt[]{b} \end{gathered}\end{gathered}

50

=5

2

a

6

=a

3

b

7

=b

3

b

Next,

5\sqrt[]{2}\cdot a^3\cdot b^3\sqrt[]{b}5

2

⋅a

3

⋅b

3

b

Reordering the expression

5a^3b^3\sqrt[]{2b}5a

3

b

3

2b

User Mike Precup
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.